Smart experience engineering to support collaborative design problems based on constraints modelling (2014)
Engineering design is a knowledge intensive process -- Experts’ experiences from different product life-cycle stages play a key role in problem solving during design decision making by linking up knowledge to find better solutions for a specific design problem -- Different approaches have been used to support Collaborative and Concurrent Product Design, such as Constraint Satisfaction Problem (CSP) modelling -- Additionally, due to the need of capitalizing these experiences, the Set of Experience Knowledge Structure (SOEKS) is used to store and manage experiences of decision making process -- However it was necessary to adapt the structure to property manage the constraints approach used in Engineering Design -- This article presents a proposed adaptation to SOEKS structure in order to be able to store and reuse CSP design experiences for further re-use and analysis of multiple experiences -- Finally, a case study is presented in order to show how the proposed approach can be used in the industrial application